Blood pressure lowering mechanisms of Kadukmy™ in essential hypertension - Mohd Zainudin, Maizura; Ismawi, Hidayatul Radziah; Abdul Razak, Tariq; Jamani, Nurjasmine Aida; Daraup, Salmi (Hindawi, 2019)
The National Health and Morbidity Survey 2011 estimated that almost half (43.5%) of Malaysian adults aged 30 and older suffer from the multifactorial disease of hypertension. Studies have shown that oxidative stress and low availability of nitric oxide (NO) result in endothelial dysfunction resulting in increase of vasoactive factors such as endothelin 1 (ET 1) and Angiotensin II (Ang II), resulting in blood pressure elevation. Piper sarmentosum (PS) is a traditional Malay herbal plant known for its high total phenolic and flavonoid content. Our previous studies with Kadukmy™, our patented formulation of PS extract, have shown that its active compounds rich in antioxidant properties does not cause subacute toxicity in the haematological profile, liver and kidney in spontaneously hypertensive rats (SHRs). Our previous studies with Kadukmy™ have revealed its blood pressure lowering effects, although the exact mechanism is yet to be established. Thus, this study hopes to identify the anti-hypertensive mechanism of Kadukmy™ supplementation on the various blood pressure regulating pathways associated with the pathogenesis of essential hypertension using the Spontaneous Hypertensive Rat (SHR) model. SHR rats will be divided into 2 control groups and 2 treatment groups (Kadukmy™, Kadukmy™ + Perindopril). Blood pressure indices, biochemical levels and proteomic studies will be conducted to determine Kadukmy mechanism of action. It is hoped that the findings will provide scientific support for the patented Kadukmy to be used in hypertensive patients and encourage the culture of evidence-based medicine with local plants.